Penggunaan Aplikasi Tarteel dalam Meningkatkan Minat Belajar Tahfidz Siswa Kelas X SMAIT Daarul Hikmah Boarding School Bontang Tahun Pelajaran 2023/2024 - Aziz, Abdul; Parmono, Parmono (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
The use of the Tarteel application as an effort made by teachers to motivate students to be enthusiastic in preparing their memorization of the Al-Quran. This study aims to increase interest in learning tahfidz lessons at SMAIT Daarul Hikmah Boarding School by utilizing the Tarteel application. The study uses a qualitative descriptive method to describe and analyze social phenomena related to student learning motivation. The steps for using the application are that users download it via the Playstore and activate the user's email account, then select the memorization feature by turning off the eye icon at the bottom of the screen and starting to memorize by activating the microphone icon at the bottom right of the screen. The results of the study showed that interest in learning tahfidz increased as seen from the activeness of students when, so that negative habits such as laziness and sleepiness no longer exist and make teachers more enthusiastic in teaching. In conclusion, the Tarteel application is effective in increasing students' interest and quality of learning tahfidz.